PERFORMANCE EVALUATION OF AGRICULTURAL EXTENSION (Case Study: Tanjung Morawa District, Deli Serdang Regency) - Raman Nuzul (Institute of Computer Science (IOCS), 2020)
The purpose of this study is to analyze the performance of agricultural extension in Tanjung Morawa District, Deli Serdang Regency. The determination of the research area was carried out purposively, namely the research area was chosen intentionally with the consideration that the research area was a sub-district on the outskirts of Kota Medan, whose livelihoods were still based on the agricultural sector. Determination of the sample was carried out by using the census technique, namely the determination technique carried out by obtaining data from all heads of farmer groups in Tanjung Mowara. The number of research samples was 20 people. The analysis method used is the CIPP (Context, Input, Process, Product) evaluation model combined with the scoring method by asking questions to the research sample. The results showed that 4 indicators of performance achievement, namely context, input, process and product, indicated the percentage of achievement with an average of 95.66% and a value of 51.6. From these data it can be interpreted that the performance of agricultural extension in Tanjung Morawa District, Deli Serdang Regency is classified in the good category.